answersLogoWhite

0


Best Answer

3x + 6y = 5

-6x + 9y = 4 multiply by 2 the first equation

2(3x + 6y = 5)

-6x + 9y = 4

6x + 12y = 10

-6x + 9y = 4 add both equations

21y = 14 divide by 21 to both sides

y = 14/21 simplify

y = 2/3

3x + 6y = 5 replace 2/3 with x

3(2/3) + 6y = 5

2 + 6y = 5 subtract 2 to both sides

6y = 3 divide by 6 to both sides

y = 1/2

Thus, the solution point is (1/2, 2/3).

User Avatar

Wiki User

14y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: 3x plus 6y equals 5 -6x plus 9y equals 4?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 3x plus 6y plus 6x?

Well, darling, 3x plus 6y plus 6x simplifies to 9x + 6y. That's all there is to it, sugar. Math doesn't have to be complicated, just like your love life!


4x plus 6y equals 62 and -6x plus 6y equals -18?

4x+6y=62 -6x+6y=-18 what is the ordered pair


Solve the system of equations 3x - 6y equals 30 y equals -6x plus 34?

x = 6 and y = -2


How many values of x and y satisfy the equations 2x plus 6y equals 12 and 3x plus 9y equals 18?

2X + 6Y = 12 3X + 9Y = 18 try elimination - 3(2X + 6Y = 12) 2(3X + 9Y = 18) - 6X - 18Y = - 36 6X + 18Y = 36 ================= I will say this system is dependent and an infinite number of solutions can be found.


6x - 6y plus 11 equals 17 9y equals 3x plus 15 Solve the system of equations and enter the solution as an ordered pair?

(0,7)


What is 3x plus 5y equals 16 plus -3x -6y equals -15?

no


What is this equation in standard form 3x equals 6y plus 8?

3x-6y=-8


What is 6y-4 equals 3x in standard form?

6y = 3x + 4 y = 3/6x + 4/6 or y = x/2 + 2/3


What is the ordered pair of 3x plus 6y equals 36 3x-6y equals 0?

3x + 6y = 363x - 6y = 0 add both equations6x = 36x = 63x - 6y = 03(6) - 6y = 018 - 6y = 018 = 6y3 = yThe solution point is (6, 3).


What is this expression but simplified 3x minus 4y minus x plus 6y plus 2 plus 4x?

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2


What is the slope of -x plus 6y 12?

The slope of -x plus 6y is equals to 12 is said to be (2 + 1/6x).


What is 6x plus 3y plus 6y-2x?

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y